Latex and a ZnO-based multi-functional material for cardiac implant-related inflammation. (6th August 2019) - Zhang, Wei; Hu, Jinzhu; Zhou, Yan; Chen, Yutong; Yu, Fen; Hong, Can; Chen, Liming; Xin, Hongbo; Hong, Kui; Wang, Xiaolei
Abstract : A new memory latex foam with ZnO modification was developed to reduce the incidence of both bacteria- and shaking-induced pocket inflammation. Abstract : Cardiac pacemakers are the main implant devices for cardiovascular diseases, and their utilization and consequently the number of cases of inflammation caused by these devices are increasing year by year. Although few antibacterial treatments have been proposed for pacemakers, the rate of cardiac pacemaker-related inflammation still exhibits an abnormal increase. By analyzing the statistical reports of the inflammation at different time stages caused by pacemakers, herein, we proposed a new hypothesis to explain this unusual phenomenon. That is, in addition to bacterial infection, the long-term stimulation caused by the frequent shaking of the pacemakers in the subcutaneous tissue "pocket" may be an important hidden factor of the inflammation. This assumption was then preliminarily confirmed through the animal-shaking model. Accordingly, we developed a new memory latex foam with ZnO surface modification (LFZ), which was incorporated with a slow springback, soft cushion and broad spectrum antibacterial properties. The subsequent animal experiments demonstrated that the incidence of both bacteria- and shaking-induced tissue inflammations could be fundamentally reduced through this multifunctional LFZ-based strategy.